Study on sediment characteristics and prediction of sediment load at Galing River - Mohd Hafiz Shafiq, Jilani (2018)
A study on sediment was conducted at the various station in Galing River. There were three secondary data and one new data that will used in this research. Secondary data was consumed from three different days in order to take the samples which are 28/02/13, 13/03/13 and 27/03/13 and the latest data was conducted on 15/11/2017. This study was conducted to determine the sediment characteristic such as sediment concentration, size, density, and sediment load with the factors influencing sediment transportation. Four sampling stations were chosen, the first one with to data at upstream Galing River (Station 1 and Station 4), mid-stream Galing River (Station 2) and downstream Galing River (Station 3). Parameter were collected at the station, such as river discharge values or flow rate, depth and wide of river and the density of the river. In this study, sediment grain size is acquired through sieve analysis. For sediment concentration (mg/L), it is measured by Total Suspended Solid (TSS). While, sediment load is calculated by using Duboy’s sediment transport function. It is preferred to use Duboy’s as all samples passed this function's requirement compare than other function. Duboy’s function required median size (D50) and mean grain size (Dm). Overall, the findings of the study show that the sizes of sediment at Galing River based on Wentworth scale fall between (0.71 to 1.0mm) which indicates coarse sand type and has one sizes between (1mm to 2mm) which indicates very coarse sand. On the other hand, the average suspended sediment concentration recorded for each station shows varying values. The values were 0.010mg/L at Station 1, 0.022mg/L at Station 2, 0.015mg/L at Station 3 and 0.034mg/L at Station 4. For sediment load, the values were the highest at the station between four different days at Station 1, Station 2, Station 3 and Station 4 were 0.8009 kg/sec-m, 0.8500kg/sec-m, 5.8442kg/sec-m and 0.5222 kg/sec-m respectively. Lastly, factors influencing sediment transportation at Galing River were identified where the factors are size of sediment, rainfall, vegetal covers, human's activities (effluent and garbage), river's hydraulic (flow rate), soil erosion and river's geometric (width and depth).